1989
DOI: 10.1200/jco.1989.7.10.1407
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical modulation of fluorouracil: evidence of significant improvement of survival and quality of life in patients with advanced colorectal carcinoma.

Abstract: The purpose of this study was to evaluate the effectiveness of several new approaches designed to enhance the activity of fluorouracil (5-FU) in the management of advanced colorectal cancer. A total of 429 patients were randomized to one of the following regimens: single-agent 5-FU, given by standard 5-day, intensive-course intravenous bolus technique; 5-FU plus high-dose folinic acid (leucovorin) or 5-FU plus low-dose leucovorin; 5-FU plus high-dose methotrexate (MTX) with oral leucovorin rescue; 5-FU plus lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
272
3
19

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 813 publications
(300 citation statements)
references
References 13 publications
6
272
3
19
Order By: Relevance
“…As shown in Figure 8, when all hospital components of treatment were accounted for (with the exclusion of pharmacy resources), the monthly cost of raltitrexed was considerably lower than that of the de Gramont regimen (5-FU 400 mg m-2 bolus + LV 200 mg m-2 2-h infusion, followed by 22-h infusion of 5-FU 400 mg m-2 for 2 days every 2 weeks) (de Gramont et al, 1995) and similar to those of the Mayo regimen (bolus 5-FU 425 mg m-2 + low-dose LV 20 mg m-2 for 5 days every 4-5 weeks) (Poon et al, 1989) and a continuous ambulatory infusional regimen (5-FU 300 mg m-2 per day). Total costs were as follows: Mayo regimen £954.03 (mean) and £659.68 (median); raltitrexed £1117.85 (mean) and £959.34 (median); continuous ambulatory 5-FU £1207.61 (mean) and £749.19 (median); and de Gramont £2028.52 (mean) and £1775.66 (median).…”
Section: Other Chemotherapy Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 8, when all hospital components of treatment were accounted for (with the exclusion of pharmacy resources), the monthly cost of raltitrexed was considerably lower than that of the de Gramont regimen (5-FU 400 mg m-2 bolus + LV 200 mg m-2 2-h infusion, followed by 22-h infusion of 5-FU 400 mg m-2 for 2 days every 2 weeks) (de Gramont et al, 1995) and similar to those of the Mayo regimen (bolus 5-FU 425 mg m-2 + low-dose LV 20 mg m-2 for 5 days every 4-5 weeks) (Poon et al, 1989) and a continuous ambulatory infusional regimen (5-FU 300 mg m-2 per day). Total costs were as follows: Mayo regimen £954.03 (mean) and £659.68 (median); raltitrexed £1117.85 (mean) and £959.34 (median); continuous ambulatory 5-FU £1207.61 (mean) and £749.19 (median); and de Gramont £2028.52 (mean) and £1775.66 (median).…”
Section: Other Chemotherapy Regimensmentioning
confidence: 99%
“…Although the optimal treatment regimen for these two drugs has not been unequivocally defined, the Mayo regimen of 5-FU and low-dose LV is widely regarded as an acceptable treatment and is the only regimen to have demonstrated a significant survival advantage over unmodulated 5-FU (Poon et al, 1989). However, other combination regimens, such as the Machover (5-FU with high-dose LV) regimen (Machover et al, 1986), or continuously infused 5-FU (Seifert et al, 1975;Lokich et al, 1989;de Gramont et al, 1995) are also used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mucositis may be the dose-limiting toxicity with a variety of regimens. As many as 80% of patients receiving 5-fluorouracil and folinic acid may develop mucositis and, in up to 26%, this may be severe (Poon et al, 1989). Ulceration of the oropharynx with consequent dysphagia reaches its peak 10 or so days after chemotherapy.…”
mentioning
confidence: 99%
“…5FU/LV combination therapy has been demonstrated to improve survival and quality of life in CRC patients. 34 Pre-clinical studies have demonstrated that TS expression is a key determinant of 5FU sensitivity, 35 and multiple clinical investigations have demonstrated an improved response to 5FU-based therapy in patients with low TS expression in their tumours. 31,36 In addition, several studies have demonstrated that patients with high TS expression in their tumours have a significantly worse clinical outcome than those with low TS irrespective of response to treatment, therefore TS may also be a valuable prognostic marker.…”
Section: -Fluorouracil (5fu)mentioning
confidence: 99%